Effects of site improvement technique on seismic performance of geotechnical structures - Demirtaş, Bilge Sultan. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2022., 2022)
Earth-retaining structures are widely used in the man-made environment and compose the significant constituents of infrastructural systems worldwide. Besides, they have been constructed broadly in seismically active regions. Earthquakes can cause a lot of damage to geotechnical structures. The prevention of failures in these structures is an important issue. Cost effective remedies can be applied to retaining structures in order to prevent them from failing under seismic loading. The use of lightweight materials behind the wall as a cushion layer is one of the methods to improve the seismic performance of the retaining system. The objective of this thesis is to investigate the effects of cushion type on the seismic performance of retaining walls by performing shake table tests. The experiments were carried out with a 1/25 scaled retaining wall model with or without a cushion layer. In the experimental study, the cushions were considered as EPS geofoam and a mixture of tire crumb and sand. Additionally, various parameters, such as cushion thicknesses, EPS geofoam densities, mixture ratios of sand-tire crumb mixture, and input characteristics, are also evaluated. The results were examined by comparing the cases having a cushion layer with the case without a cushion layer depending on mentioned parameters. The evaluation of the results indicates that the seismic performance of the retaining wall is very sensitive to cushion type. It is observed that the EPS cushions are more effective than the sand-tire crumb mixtures to improve the seismic performance of the wall. Additionally, the use of cushion layer with higher thickness can be an effective solution to improve the seismic performance of the retaining wall, prevent the future failure of the retaining structure, and mitigate earthquake hazards.
Keywords: Geotechnical engineering.; Retaining walls.